Correction of 2D Isodose Curve on the Sloping Surface using Tissue Air Ratio (TAR) Method - Nuzula, Nurul Firdausi; Adi, Kusworo; Anam, Choirul (JURNAL SAINS DAN MATEMATIKA, 2015)
The curve of 2D isodose is used to determine the dose distribution in patient treated by radiotherapy. Therefore, isodose curve is very useful for planning and evaluating of the dose received by the patient. Correction of 2D isodose curve for sloping surface is very important due to the skin of patient is not flat. In this study, the correction of isodose curve was calculated using tissue air ratio (TAR) method for radiation field size of 10x10 cm2. The correction factor was obtained by comparison of TAR value for effective depth and TAR value for total depth. The correction factor then was multiplied to isodose curve for flat surface. In this study, the software for calculating the automated correction factor due to sloping of patient surface has been successfully developed. It was found that if the sloping of patient surface increases then the corrected isodose curve increases. Key wods: 2D isodose curve, tissue air ratio (TAR), correction factor, sloping patient surface.